Tau accumulation is cleared by the induced expression of VCP via autophagy - Giong Hoi-Khoanh; Hyeon Seung Jae; Lee Jae-Geun; Cho Hyun-Ju; Park Uiyeol; Stein Thor D.; Lee Junghee; Yu Kweon; Ryu Hoon; Lee Jeong-Soo (Springer Verlag, 2024)
Tauopathy, including frontotemporal lobar dementia and Alzheimer's disease, describes a class of neurodegenerative diseases characterized by the aberrant accumulation of Tau protein due to defects in proteostasis. Upon generating and characterizing a stable transgenic zebrafish that expresses the human TAUP301L mutant in a neuron-specific manner, we found that accumulating Tau protein was efficiently cleared via an enhanced autophagy activity despite constant Tau mRNA expression; apparent tauopathy-like phenotypes were revealed only when the autophagy was genetically or chemically inhibited. We performed RNA-seq analysis, genetic knockdown, and rescue experiments with clinically relevant point mutations of valosin-containing protein (VCP), and showed that induced expression of VCP, an essential cytosolic chaperone for the protein quality system, was a key factor for Tau degradation via its facilitation of the autophagy flux. This novel function of VCP in Tau clearance was further confirmed in a tauopathy mouse model where VCP overexpression significantly decreased the level of phosphorylated and oligomeric/aggregate Tau and rescued Tau-induced cognitive behavioral phenotypes, which were reversed when the autophagy was blocked. Importantly, VCP expression in the brains of human Alzheimer's disease patients was severely downregulated, consistent with its proposed role in Tau clearance. Taken together, these results suggest that enhancing the expression and activity of VCP in a spatiotemporal manner to facilitate the autophagy pathway is a potential therapeutic approach for treating tauopathy.